PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE (2017-2019) - Astami, Dwi; Sudibyo, Tyagita Dianingtyas (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2021)
Economic growth in this era of globalization is very difficult to predict in Indonesia. In fact, during the current pandemic, quite many companies experienced income degradation due to drastic decline in productivity and export-import activities. With this the company must be able to maintain its existence in order to achieve the goals of the company. To be able to achieve these goals, companies must increase profits or profits in order to reflect the maximum company value. Company value is a form of good name or achievements obtained by the company when carrying out activities within a certain period. The purpose of this study is to test empirically the effect of profitability, capital structure and investment decisions on the value of the transportation sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The period used in this research is 2017-2019. This type of research is a quantitative study with a causal associative research design. The population of this research is the transportation sub-sector manufacturing companies that have gone public, are active and listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique was purposive sampling method and the research data were obtained 15 companies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results showed: ROE (Return on Equity) has a significant and significant effect on Price to Book Value (PBV). ROA (Return on Asset) has no significant effect on PBV (Price to Book Value). DER (Debt to Equity Ratio) has a significant effect on PBV (Price to Book Value). PER (Price Earnings Ratio) has a significant and significant effect on Price to Book Value (PBV). From the results of the F test, it was found that the F table value was 179,100 with a Sig. 0,000. Which means the independent variable has a simultaneous effect and can be used to predict the dependent variable. The Adjusted R Square value is 0.942, which means that PBV is influenced by ROE, ROA, DER, and PER of 94.2% and the remaining 5.8% is explained by other variables outside the model.